Cadeias de tensão: repertórios disciplinares de facções e do sistema em unidades de internação alagoanas - Carvalho, Ada Rizia Barbosa de (2021)
This paper deals with the tensions between disciplinary repertoires in Alagoas detention unities, mobilized in the institutional dynamics, by employees, and in the enunciations, performances and senses of belonging of young inmates to the symbols expressed by the abbreviations PCC and CV. This is the result of an ethnographic research. For this purpose, the dialogues established with adolescents and employees in the socio-educational system of Alagoas are used, aiming to embrace both perspectives and differentiate them. In addition, documents – institutional records – produced by employees in a period between 2004 and 2016 are also analysed. It is understood, through a figurative perspective of Eliasian inspiration, that the interactions between adolescents and employees – that are interconnected through the most varied positions in the detention unities and through their interlacing with the worlds of urban peripheries – make possible the mobilization constraints and pressures, of agencies and positions taken, which are evident both in disciplinary repertoires and in confrontations with them. It is argued that their positions and actions can only be understood in the interdependencies, in the mutual pressures of one another. In the system, institutional and criminal repertoires are inseparable, reproduce and feed back each other.